IMPROVING STUDENT LEARNING OUTCOMES IN STATISTICS FOR RESEARCH EDUCATION COURSES USING MOODLE PLATFORM DURING PANDEMIC - Tanti Listiani (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
Currently, the education system is experiencing a situation that requires teachers to be able to master distance learning media, especially during this Covid-19 pandemic outbreak. The distance education system is one of the solutions to overcome difficulties in face-to-face learning with the existence of social distancing rules considering the problems of time, location, distance, and cost which are major obstacles at this time. Moodle is a platform that can be used for distance learning. This study aims to see whether there is an increase in student learning outcomes in studying educational research statistics using the Moodle platform. The type of research is classroom action research with the Pelton model. This research sample is 42 students who take education research statistics courses. The sample data was processed using descriptive statistics taken from student learning outcomes. The results showed that student learning outcomes in studying educational research statistics have increased. The Moodle platform can help students get more learning outcomes, and it is effectively used as a solution in distance lectures. Suggestions for further research are the need for improvisation in using the Moodle platform to maximize its use